2019
DOI: 10.1186/s13102-019-0133-9
|View full text |Cite
|
Sign up to set email alerts
|

Improved maximal strength is not associated with improvements in sprint time or jump height in high-level female football players: a cluster-randomized controlled trial

Abstract: Background Maximal strength increments are reported to result in improvements in sprint speed and jump height in elite male football players. Although similar effects are expected in females, this is yet to be elucidated. The aim of this study was to examine the effect of maximal strength training on sprint speed and jump height in high-level female football players. Methods Two female football teams were team-cluster-randomized to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…The selected studies were submitted to the PEDro methodological quality scale. Two studies obtained a score of 9/10 [ 36 , 37 ], one study obtained 8/10 [ 38 ], six obtained 7/10 [ 5 , 6 , 39 , 40 , 41 ], two obtained 5/10 [ 42 , 43 ], and two obtained 4/10 [ 44 , 45 ]. Table 1 displays the complete and detailed PEDro scale score of each study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The selected studies were submitted to the PEDro methodological quality scale. Two studies obtained a score of 9/10 [ 36 , 37 ], one study obtained 8/10 [ 38 ], six obtained 7/10 [ 5 , 6 , 39 , 40 , 41 ], two obtained 5/10 [ 42 , 43 ], and two obtained 4/10 [ 44 , 45 ]. Table 1 displays the complete and detailed PEDro scale score of each study.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of ST is to promote maximal strength and muscular hypertrophy to improve physical performance [ 22 ], and this method has often been used by physical trainers in soccer training routines [ 7 , 47 ]. Two studies by Pardos-Mainer et al [ 5 , 6 ] found that ST exerted a borderline small–moderate effect on vertical jump performance whilst Lindblom et al [ 39 ] and Pedersen et al [ 38 ] resulted only a trivial ES, and even the effect was negative. It is possible that the exercises included in the ST programs do not demonstrate a significant transference effect to soccer-specific physical performance and conditioning programs with higher load and intensity would be necessary in order to benefit from the training [ 8 , 35 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the dynamic strength measurements, the participant was asked to perform three CMJs, with a 1-min rest in between, on a transportable force platform (Quattro Jump, Kistler GmbH, Winterthur, Switzerland, 500 Hz recording frequency). Start and end position was upright, in a hip-wide standing position, with hands placed on the hips [ 16 ]. The hands were not allowed to be moved during the whole measurement, in order not to influence the jump height [ 17 ].…”
Section: Methodsmentioning
confidence: 99%